Larrea divaricata volatilome and antimicrobial activity against Monilinia fructicola - Boiteux, Joana Jaqueline (2018)
Monilinia fructicola is the most destructive pre- and postharvest pathogen in stone fruit worldwide. A great attention has been paid to plant extracts, a rich source of bioactive chemicals, for the sustainable pest control. Volatile organic compounds from plant matrices have proved important antimicrobial activity. In the present work, an analytical procedure for the characterization of the volatile profile in L. divaricata extract by headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography/mass spectrometry (GC–MS) was proposed. Moreover, the biological activity of L. divaricata extract was evaluated for their contact-phase and vapor-phase effects on M. fructicola mycelial growth. In order to improve the absorption of volatile compounds, the following experimental parameters were optimized: fiber coatings, time and temperature extraction. As a result of the optimization, CAR/PDMS fibers, 30 °C and 30 min were selected for the extraction volatile compounds from L. divaricata extract. A total of 79 VOCs were identified in the extract. Among them, aromadendrene was found at highest concentration. Other bioactive volatile compounds were detected such as eugenol, carvacrol, limonene and thymoquinone. The antimicrobial activity of L. divaricata extract on M. fructicola mycelial growth was evaluated under contact- and vapor-phase conditions. L. divaricata extract showed significant antimicrobial activity on M. fructicola mycelial growth in both conditions. The results reveal that L. divaricata is a promising antifungal agent which could be used as bio-fungicide in the protection of fruits and vegetables against postharvest infections.